2019
DOI: 10.1111/1759-7714.12981
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between EGFR mutation status and F18‐fluorodeoxyglucose positron emission tomography‐computed tomography image features in lung adenocarcinoma

Abstract: Background The purpose of this study was to investigate an association between EGFR mutation status and 18 F‐fluorodeoxyglucose positron emission tomography‐computed tomography ( 18 F‐FDG PET‐CT) image features in lung adenocarcinoma. Methods Retrospective analysis of the data of 139 patients with lung adenocarcinoma confirmed by surgical pathology who underwent preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…This is a complex issue, with numerous factors involved, including tumor stage, co-morbidities, age, performance status, and tumor mutational state. Metabolic activity may not predict the presence of mutations in cancer genes, such as EGFR [18,19]. Consistent with these reports, no significant relationship between EGFR mutation status and SUV was observed in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…This is a complex issue, with numerous factors involved, including tumor stage, co-morbidities, age, performance status, and tumor mutational state. Metabolic activity may not predict the presence of mutations in cancer genes, such as EGFR [18,19]. Consistent with these reports, no significant relationship between EGFR mutation status and SUV was observed in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…When combining with other accessible factors, an AUC of predicting EGFR mutations could reach 0.84. Several studies [8,[12][13][14][15][16][17][18][19][20][21][22][23] had evaluated the value of FDG uptake for predicting EGFR status in NSCLC. As described in Table 3, the results were not very consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all previous studies solely focused on the pSUVmax. Ten of them [8,[14][15][16][18][19][20][21][22][23] revealed that lower pSUVmax was associated with EGFR mutations, and three studies [8,22,23] found lower pSUVmax was an independent predictor for EGFR mutations by multivariate analysis. Meanwhile, two studies [15,19] demonstrated that high pSUVmax was a significant predictor of EGFR mutations, and one [14] didn't show statistical difference in pSUVmax between different EGFR statuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Previous studies have shown that 18 F-FDG uptake was associated with genetic alterations in NSCLC, such as KRAS and EGFR mutation. [28][29][30] CD147 as a tumor-associated antigen is highly enriched on the surface of various malignant tumor cells, such as Figure 4 CD147 promoted 18F-FDG uptake in human LUAD cell lines and LUAD xenograft models. (a, b) CD147 promoted 18F-FDG uptake by both stable HCC827 and H1975 cell lines with different CD147 expression levels.…”
Section: Discussionmentioning
confidence: 99%